2012
DOI: 10.1186/1746-6148-8-247
|View full text |Cite
|
Sign up to set email alerts
|

Carprofen for perioperative analgesia causes early anastomotic leakage in the rat ileum

Abstract: BackgroundThere is increasing evidence that perioperative use of NSAIDs may compromise the integrity of intestinal anastomoses. This study aims to characterize the negative effects of carprofen on early anastomotic healing in the rat ileum.ResultsIn 159 male Wistar rats an anastomosis was constructed in the ileum. In experiment 1 eighty-four rats were divided over control and experimental groups, which received daily buprenorphine or carprofen, respectively, as an analgesic and were killed on day 1, 2 or 3 aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Later, it was used in animals to treat pain and inflammation. The incidence of GIT side effects with carprofen resembles those of other nonselective COX inhibitors [16,17].…”
Section: Introductionmentioning
confidence: 91%
“…Later, it was used in animals to treat pain and inflammation. The incidence of GIT side effects with carprofen resembles those of other nonselective COX inhibitors [16,17].…”
Section: Introductionmentioning
confidence: 91%
“…There are however potential side effects to the use of NSAID, such as gastric ulceration and other 51 gastrointestinal complications (Engelhardt et al, 1995a, Engelhardt et al, 1995b, van der Vijver et al, 2012, and these factors should be taken into account when determining the most effective analgesic agent for a particular surgical procedure.…”
Section: Nsaids Provides An Alternative Analgesic Agent To Opioid Drugsmentioning
confidence: 99%
“…64 Interestingly, in rat models, the addition of the NSAID carprofen significantly impaired the healing in ileal anastomoses (but not colocolonic) in two studies. 65,66 Of course, there have also been papers that have concluded that there is no increase in anastomotic leak with NSAID usage. 67,68 In a recent metanalysis of NSAID usage and anastomotic leaks, the authors concluded that most studies, which indicate an association of NSAIDs with anastomotic leak are flawed but, that there is still concern regarding NSAID use and leak.…”
Section: Nsaidsmentioning
confidence: 99%